Culinary Art and Anthropology - Adapon Joy (Berg, 2008)
This book offers a sensual, theoretically sophisticated model for understanding food anthropologically. Illustrations, Preface, Perceptions of Mexican Cuisine, Cooking as an Artistic Practice, Barbacoa in Milpa Alta, Women as Culinary Agents, Mole and Fiestas, The Centrality of Gastronomy in Social Life, Notes, Work Cited, Index.